Pertumbuhan dan Hasil Tiga Varietas Mentimun (Cucumis sativus L.) Pada Medium Hidroponik Tertentu - Zuyasna Zuyasna; Zaitun Zaitun; Sri Alfina (Jurnal Agrista, 2009)
Growth and Cucumber Yield of Three Different Varieties on Selected Hydroponic MediumABSTRACT. The subjective of this study were to investigate several varieties and medium on the growth and the yield of cucumber. The research was conducted at the screen house Agriculture Faculty, Syiah Kuala University Darussalam – Banda Aceh from August to December 2008. Randomized completely block design with two factors was used on this experiment using three replications. The first factor was medium for hydroponic (i.e. sand, rice chaff charcoal, and sawdust), and the second factor was cucumber variety (i.e. Dinasty, Baby, and Venus). Each of unit experiment used 2 plants, and meaning that we used 54 plants for this experiment. The result showed that he medium significantly influenced the cucumber weight per plant, influenced the stem diameter on 45 days after planting (DAP), but not for other parameters (i.e. the plant height on 15, 30 and 45 DAP ; the stem diameters on 15 and 30 DAP ; the fruit length ; the fruit diameter and the amount of fruit per plant). The variety significantly influenced the fruit length and the cucumber weight per plant, however the variety not significantly influenced other parameters (i.e. the plant height on 15, 30, and 45 DAP; the stem diameter on 15, 30, and 45 DAP; the amount of fruit per plant; and the fruit diameter). We found that the interaction between the medium and the variety occurred on the cucumber weight per plant.